Understanding factors associated with re-referral of youth for commercial sexual exploitation. (July 2021) - Kafafian, Matthew; de Vries, Ieke; Farrell, Amy; Goldfarb, Susan; Bouchard, Elizabeth
Abstract: Background: Since the passage of the Victims of Trafficking and Violence Prevention Act of 2000 in the United States, awareness has increased about the problem of commercial sexual exploitation of children (CSEC). Moreover, United States Federal law calls upon child welfare agencies to establish policies and practices that help identify and provide services to minors at risk of CSEC. Although awareness has increased about the problem of CSEC, little attention has been paid to understanding why some youths are re-referred to CSEC programs after initial referral and intervention. Objective: The present study examines which factors drive re-referrals of youths for CSEC concerns. Participants and setting: Data about a population of high-risk youths ( n = 416) referred to a CSEC-specific program in the Northeast of the United States between 2011 and 2018. Methods: Using logistic regression analyses, we investigate what factors are associated with youth having multiple referrals. Results: Youths with multiple referrals were more likely to have histories of missing from care ( OR = 2.996, p  < 0.001), substance misuse ( OR = 2.802, p  < 0.01), and greater agency involvement ( OR = 1.260, p  < 0.05). However, youths with multiple referrals were not at heightened risk of CSEC as compared to youths that were not re-referred. Conclusion: The results demonstrate that re-referred youths meet the profile of a victim as depicted on screening and assessment instruments, which has important implications for victim services and referral systems dedicated to identifying CSEC and protecting youths who may experience re-victimization for CSEC.